2020
DOI: 10.1016/j.psj.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of commercial feed dilution with copra meal or cassava leaf meal and enzyme supplementation on broiler performance

Abstract: A preliminary study investigated the impact of commercial feed dilution with copra meal ( CM ) or cassava leaf meal ( CLM ) and enzyme supplementation on broiler performance. Commercial feed alone (control) or diluted with CM and CLM at a concentration of 100 and 200 g/kg in the starter and finisher diets, respectively, was fed without and with Challenzyme 300A at a concentration of 300 g/tonne in 2 × 2 factorial arrangements with a control. Two hundred, 7-day-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The beneficial effect of enzymes products on transit time in broilers fed fibrous CM (Diarra, S. S. et al, 2015;Devi & Diarra, 2017), rye (Lázaro et al, 2003), soybean (Adeyemi et al, 2013) and de-oiled rice bran (Anuradha & Roy, 2015) diets has been reported. Similar studies on commercial diet dilution with CM (Mael et al, 2020) and CM or CLM (Diarra, S. & Anand, 2020) also reported improvement in broilers with enzyme supplementation. The pattern of WG and F/G in the main effects was not clear but this suggests the need for more studies on enzyme concentration.…”
Section: Growth Performancesupporting
confidence: 55%
See 1 more Smart Citation
“…The beneficial effect of enzymes products on transit time in broilers fed fibrous CM (Diarra, S. S. et al, 2015;Devi & Diarra, 2017), rye (Lázaro et al, 2003), soybean (Adeyemi et al, 2013) and de-oiled rice bran (Anuradha & Roy, 2015) diets has been reported. Similar studies on commercial diet dilution with CM (Mael et al, 2020) and CM or CLM (Diarra, S. & Anand, 2020) also reported improvement in broilers with enzyme supplementation. The pattern of WG and F/G in the main effects was not clear but this suggests the need for more studies on enzyme concentration.…”
Section: Growth Performancesupporting
confidence: 55%
“…Recently, Mael et al (2020) observed that the dilution of commercial feed at 100 g/ kg maintained performance and reduced the cost of producing Cobb 500 broilers, but at 200 g/kg dilution, enzyme supplementation was required. Diarra & Anand (2020) also found that both CM and CLM have potential to dilute commercial broiler feed with cost benefit. Although PKM is similar to CM and CLM in nutritional characteristics there are no reports on its use in commercial feed dilution for broilers.…”
Section: Introductionmentioning
confidence: 91%
“…Haetinger et al [ 94 ] reported a reduction in energy digestibility with inclusion of CM in diets. A positive response on growth performance and intestinal characteristics was observed when a commercial diet diluted with CM and supplemented with a cocktail of carbohydrases and protease was fed to broiler chickens in the starter and finisher phases [ 95 ]. Feeding of mannanase-hydrolyzed CM improved performance and carcass characteristics of broiler chickens [ 96 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%
“…Diet composition and physicochemical characteristics are known to influence litter quality in birds kept on the same bedding substrate (43,(110)(111)(112)(113). Viscous fibers in the diet reduce nutrient digestion and absorption (111,112,114) and increase cecal fermentation (115,116). Increased fermentation in the cecum resulting in soft feces is a major cause of wet litter in poultry houses (110).…”
Section: Some Nutritional and Environmental Factors Affecting Litter Qualitymentioning
confidence: 99%